Constelation exempt from any mithology: three latinamerican readings of portuguese poetry - Serra, Pedro (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Temporal modality that determines both an experience and an interpretation of Modernity, the sudden instant provides us with a possible figure of the contact of different Spanish and Portuguese-speaking Latin American poets with texts by Pessoa and Camões, namely Octavio Paz, Jorge Luis Borges and Paulo Henriques Britto. In this sense, my article aims to interrogate the heuristic and hermeneutical valences of the aesthetic event for the construction of a future archive of the margins of Late Modernity and to propose a decolonial perspective of the relations between Portuguese poetry and Latin America.